Potential use of Argentine kaolinite clays as pozzolanic material - Tironi, Alejandra (2014)
Different Argentine kaolinitic clays were selected to study their potential pozzolanic activity. The incidence of several factors such as the origin of deposits (primary or sedimentary clays), mineralogical composition, and the order/disorder degree of kaolinite structure on the pozzolanic activity was analyzed. Five clays were characterized by chemical analysis, X-ray diffraction (XRD), Fourier transformed infra-red spectroscopy (FTIR), differential thermal analysis combined with thermo-gravimetric analysis (DTA/TG), and Scanning Electron Microscopy (SEM). The crystallinity of kaolinite in raw clays was estimated by five indexes: FWHM-001, FWHM-002, Hinckley Index (HI), and R2 on the XRD patterns, whereas the P0 index was determined on the FTIR spectra. Clays were calcined at 700 °C and ground until all mass passed through a 45 μm sieve. Pozzolanic activity was evaluated by the Frattini test and the strength activity index (SAI) at 7, 28 and 90 days using a blended cement containing 30% by weight of calcined clay. Complementary, the presence of remaining Ca(OH)2 in mortar was checked by XRD at 28 and 90 days. Results indicate that four blended cements presented a very good pozzolanic activity evaluated by the Frattini test at 7 and 28 days and they have a Different compressive strength with a SAI N 1 at 90 days. In these blended cements, the Ca(OH)2 released by cement hydrationwas consumed. Analyzing the incidence of factors on pozzolanic activity, it can be concluded that clays containingmore than 50% kaolinite provide enough amount of reactive material, and that the rate of the pozzolanic reaction is improved when the kaolinite mineral present in the clay has a disordered structure.